Graphene Oxide Sheets Combine into Conductive Coatings by Direct Oxidative Electropolymerization - S. Halevy (Nature Portfolio, 2017)
Abstract New coatings are obtained when graphene oxide is further oxidized at moderate anodic potentials (≤~1.3 V vs. Ag/AgCl). Based on a variety of spectroscopic and electrochemical observations, the coatings are attributed to the direct electropolymerization of graphene oxide sheets via oxidation of the phenol edge groups on graphene. Depending on the applied potential, ether or carboxylic groups are formed. The coatings obtained via further oxidation are characterized by a lower O/C ratio due to decarboxylation and a higher content of C=C bonds. These bonds extend aromatic conjugation into the combined graphene oxide sheets and are responsible for the highly conductive nature of these coatings.